The Role of The Triage Nurse Deployment in Reducing Triage Time in Emergency Department - Karina, Ristanti; Basabih, Masyitoh (UI Scholars Hub, 2025)
Emergency Departments (ED) operate under high-pressure conditions where rapid and accurate triage is essential to ensure optimal patient outcomes. This study aimed to evaluate whether the assignment of dedicated triage nurses could reduce triage procedure time in the ED. The study employed an observational cross-sectional design using secondary data extracted from the Hospital Information System (HIS) at XYZ Private Hospital, Bogor. The intervention involved assigning trained triage nurses for each shift starting in June 2024, replacing the previous practice of ad hoc triage by available nurses. The results showed a significant reduction in median triage time from 4 minutes and 11 seconds to 2 minutes and 23 seconds after the intervention (p-value =